The complete Peanuts 1999-2000 - Schulz, Charles M. (Charles Monroe), 1922-2000 (Fantagraphics Books, 2016)
"This penultimate volume of The Complete Peanuts series collects the last year of the most beloved comic strip ever created. Rerun embarks on a career as an 'underground' comic book artist, and Snoopy's siblings Andy, Olaf, and Spike (who cameo in the Peanuts movie) appear. The volume is rounded out with the complete Li'l Folks. Prefiguring Peanuts and its major themes, this weekly single-panel comic Schulz produced for his hometown paper is available here for the first time outside the collector's market!" -- Back cover.